2021
DOI: 10.1108/bfj-11-2020-1040
|View full text |Cite
|
Sign up to set email alerts
|

Factors driving Thailand rice farmer decision-making in the choice of marketing channel

Abstract: PurposeSince the end of the latest rice-pledging scheme, Thai rice farmers have had more freedom in selecting marketing channels. Understanding the determinants of farmers' decision-making associated with these channels is of particular interest to multiple stakeholders in the rice value chain. This study aims to examine how economic, relational and psychological factors concurrently underpin Thai rice farmers' decision-making and influence their marketing channel choice.Design/methodology/approachDrawing on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Green consumers may be influenced by other factors too, including the range of green products offered, the availability and validity of information, and communication and claims made that are associated with the product [32]. In this regard, we share the view of Thamthanakoon et al [82] who claim that "past behaviour exerts influence on intention indirectly, through the outcomes of the appraisal of the channel used, typically including attitude toward and trust in the channel" (p. 4). To access buying behaviour, do Paço et al [32] applied ten items from the ECCB scale [29] covering issues such as right packaging, polluting, or recycling.…”
Section: Buying Behaviourmentioning
confidence: 82%
“…Green consumers may be influenced by other factors too, including the range of green products offered, the availability and validity of information, and communication and claims made that are associated with the product [32]. In this regard, we share the view of Thamthanakoon et al [82] who claim that "past behaviour exerts influence on intention indirectly, through the outcomes of the appraisal of the channel used, typically including attitude toward and trust in the channel" (p. 4). To access buying behaviour, do Paço et al [32] applied ten items from the ECCB scale [29] covering issues such as right packaging, polluting, or recycling.…”
Section: Buying Behaviourmentioning
confidence: 82%
“…J. Brown et al, 2020; Thamthanakoon et al, 2021; Vallejos et al, 2023). Ouellette and Wood (1998) conducted a meta-analytic synthesis of prior research related to past behavior, and they found that in the case of behaviors that are well practiced and performed in stable contexts, past behavior is a direct predictor of future acts.…”
Section: Literature Review and Research Hypothesesmentioning
confidence: 99%
“…Many scholars have demonstrated that the relationships between past behavior and intentions or behaviors may be direct (e.g., L. Shevlin & Goodwin, 2019) or indirect through the predictors of the model (e.g., D. J. Brown et al, 2020;Thamthanakoon et al, 2021;Vallejos et al, 2023). Ouellette and Wood (1998) conducted a metaanalytic synthesis of prior research related to past behavior, and they found that in the case of behaviors that are well practiced and performed in stable contexts, past behavior is a direct predictor of future acts.…”
Section: Past Behaviormentioning
confidence: 99%
“…According to statistics and field conditions, the effect of soil fertility and insect disturbance prevents some rice types from reaching their maximum value (or ideal). Despite the fact that it is impacted by water availability, planting intensity cannot be maximized 70 .…”
Section: Limitation Of Rice Production Modelling In Fieldmentioning
confidence: 99%